Porównanie wyników klasyfikacji nauczycieli akademickich pod względem wpływu osobowości na popularność wykładów ze statystyki - Machowska-Szewczyk, Małgorzata (Comparison of Classification Results of University Teachers Regarding Personality Influence on Popularity of Statistics Lectures, 2008)
In the article the classification results which use objects described by symbolical variables with weights are compared to results of grouping based on rough sets elements. The quality research of the received divisions shows that results of didactics rate of university teachers, obtained as a result of using Ward's method to an objects collection described by symbolical variables, are more reliable than those received by decision-making rules of an approximate model of attendance.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 7, s. 240-248